2019
DOI: 10.3389/fpsyg.2019.01036
|View full text |Cite
|
Sign up to set email alerts
|

Using a Situation Awareness Approach to Identify Differences in the Performance Profiles of the World’s Top Two Squash Players and Their Opponents

Abstract: Purpose The pressure exerted on a squash player is a consequence of the quality of a shot coupled with the ability of the player to return the ball, namely, the coupling of the two players’ situation awareness (SA) abilities. SA refers to an awareness of all relevant sources of information, the ability to synthesize this information using domain knowledge and the ability to physically respond to a situation. Methods Matches involving the two best players in the world ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The findings of our literature search revealed that Distributed Situation Awareness (DSA) and Endsley's (1995b) three-level frameworks were the overwhelming SA frameworks discussed in a sporting context. Four articles described Endsley's (1995b) three-level framework (Caserta & Singer, 2007;Knez & Ham, 2006;Murray, 2018;Ng et al, 2013). Four articles employed the framework of DSA to a variety of sports which included research on athletes, coaches, and officials (Macquet & Stanton, 2014;Salmon et al, 2017).…”
Section: Situation Awareness Framework In Sportsmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings of our literature search revealed that Distributed Situation Awareness (DSA) and Endsley's (1995b) three-level frameworks were the overwhelming SA frameworks discussed in a sporting context. Four articles described Endsley's (1995b) three-level framework (Caserta & Singer, 2007;Knez & Ham, 2006;Murray, 2018;Ng et al, 2013). Four articles employed the framework of DSA to a variety of sports which included research on athletes, coaches, and officials (Macquet & Stanton, 2014;Salmon et al, 2017).…”
Section: Situation Awareness Framework In Sportsmentioning
confidence: 99%
“…Endsley's (1995b) three-level framework was described in four papers investigating SA in cyclists (Knez & Ham, 2006), tennis players (Caserta & Singer, 2007), basketball players (Ng et al, 2013), and squash players (Murray, 2018). As mentioned previously, Endsley's (1995b) three-level framework contains hierarchal levels of perception, comprehension, and projection.…”
Section: Three-level Frameworkmentioning
confidence: 99%
“…As a consequence, it is possible to conclude that the studies are primarily concerned with national or international sports policy. In research on sports awareness these topics are found; situation awareness in sports (Huffman et al, 2022), cognitive skills, visual behaviors, decision-making, foresight (Caserta and Singer 2007;McCrozier et al, 2015;McGuckian et al, 2020;Murray, 2018), etc. It has been monitored that studies have been realized on these subjects.…”
Section: Introductionmentioning
confidence: 99%
“…e key performance indicators of badminton are mainly reflected in the use of court areas, stroke distribution, technical movements, and stroke effectiveness. Like tennis [5][6][7], squash [8][9][10], and table tennis [11][12][13], the key performance indicators are mainly reflected in tactics. A successful badminton matchup will hold the opponent in spatial pressure to hit the badminton to the opponent's most disadvantageous area.…”
Section: Introductionmentioning
confidence: 99%